Visibility graph-based path-planning algorithm with quadtree representation. (December 2021) - Lee, Wonhee; Choi, Gwang-Hyeok; Kim, Tae-wan
Abstract: In recent years, unmanned surface vehicles (USVs) have been widely used in various applications. To fulfill target missions, USVs must be able to plan their path to the destination. Although many path-planning methods have been developed, most are inappropriate for application in complex marine environments. In this study, we propose a novel path-planning algorithm, which combines the merits of quadtree representation and visibility graphs, for efficient path planning of USVs in complex marine environments. Quadtree representation reduced the computation time and memory consumption. Additionally, the wind and wave data were considered to shorten the voyage time from the departure to destination points. Furthermore, the Dijkstra algorithm was applied to the quadtree to determine the suboptimal path. We then constructed a visibility graph with path waypoints using an improved line-of-sight algorithm to perform path planning on the visibility graph. The proposed algorithm not only facilitates path planning with minimum voyage time but also maintains the USV clearance distance from the coastline. To verify the performance, the proposed algorithm was compared with other methods for South Korean case studies. Overall, the proposed algorithm was able to generate a high-quality suboptimal path for the USV within a short time span.